UKURAN KANTOR AKUNTAN PUBLIK, DISCRETIONARY ACCRUALS DAN OPINI AUDIT GOING CONCERN - Ravaela Amba Masiku; Christine Novita Dewi (Jurnal Riset Akuntansi dan Keuangan, 2019)
The purpose of this study is to examine auditor’s concervatism in term of their reaction to client’s earnings management behavior and their limitations to issue the going concern opinions (GCO). The population of this study consists of 672 observations from 69 companies are listed on the Indonesia Stock Exchange (BEI) during 2012-2017. The author used the modified Jones model to measure discretionary accruals as a proxy of earnings management. The results of this study indicate that size of audit firm has a positive effect to discretionary accrual. Companies that have been audited by the Big4 tend to apply discretionary accrual in their financial reporting than companies audited by Non-Big4. Further, to strenghten the first hypothesis, we examine the effect of discretionary accruals and going concern opinion on companies that audited by audit firms Big4 lower than companies that audited by audit firms Non-Big4. We found that the result is consistent with the first hypothesis. Keywords : auditor reputation, discretionary accruals, going concern opinion, audit firm  ABSTRAK Tujuan dari penelitian ini adalah untuk menguji konservatisme auditor dalam hal reaksi auditor terhadap akrual diskresioner yang dilakukan oleh perusahaan dan keterbatasan auditor untuk menerbitkan opini Going Concern (GC). Populasi penelitian terdiri dari 672 pengamatan dari 69 perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) selama tahun 2012-2017. Penulis menggunakan model modifikasi Jones untuk mengukur akrual diskresioner sebagai proksi manajemen laba. Hasil dari penelitian ini menjelaskan bahwa ukuran kantor akuntan publik berpengaruh positif terhadap akrual diskresioner, hal tersebut diperkuat dengan pengaruh akrual diskresioner dan opini audit going concern yang diaudit oleh kantor akuntan publik Big4 lebih rendah dari perusahaan yang tidak diaudit oleh kantor akuntan publik Non-Big4. Kata kunci : reputasi auditor, akrual diskresioner, opini audit going concern, kantor akuntan publik